How Do Females With PTSD and Substance Abuse View 12-Step Groups? An Empirical Study of Attitudes and Attendance Patterns. (6th December 2015) - Najavits, Lisa M.; de Haan, Hein; Kok, Tim
Abstract : Background. Self-help groups are beneficial for many people with addiction, predominantly through 12-step models. Yet obstacles to attendance also occur. Objectives. We explored attendance patterns and attitudes toward self-help groups by 165 outpatient females with co-occurring posttraumatic stress disorder (PTSD) and substance use disorder (SUD), the first study of its kind. Methods. Cross-sectional self-report data compared adults versus adolescents, and those currently attending self-help versus not attending. We also explored attendance in relation to perceptions of the PTSD/SUD relationship and symptom severity. Results. Adults reported higher attendance at self-help than adolescents, both lifetime and currently. Among current attendees, adults also attended more weekly groups than adolescents. Yet only a minority of both age cohorts attended any self-help in the past week. Adults perceived a stronger relationship between PTSD and SUD than adolescents, but both age groups gave low ratings to the fact that self-help groups do not address PTSD. That item also had low ratings by both those currently attending and not attending self-help. Analysis of those not currently attending identified additional negative attitudes toward self-help (spirituality, addiction as a life-long illness, sayings, and the fellowship). Symptom severity was not associated with attendance, but may reflect a floor effect. Finally, a surprising finding was that all-female groups were not preferred by any subsample. Conclusions/Importance. Creative solutions are needed to address obstacles to self-help among this population. Addressing trauma and PTSD, not just SUD, was valued by females we surveyed, and may be more helpful than all-female groups per se.